2006
DOI: 10.1111/j.1399-0039.2006.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiple sclerosis after vaccination against hepatitis B: a study based on human leucocyte antigen haplotypes

Abstract: The aetiology of multiple sclerosis (MS) is still not fully understood. Infectious agents are believed to play a role in the development of this multifactorial disease. Cases in which this disease occurs after administration of both plasma-derived and recombinant hepatitis B vaccines have been reported. In this study, we compared a group of 11 MS patients who developed first clinical symptoms after hepatitis B vaccination (group I) with 71 MS patients who were never vaccinated against hepatitis B and were nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although some studies have suggested an association between hepatitis B vaccination and the development of MS, a large body of research studies rejects the possibility of any association between them. [28][29][30] We also evaluated CMV in our case and control groups. While only one positive CMV infection was detected in the control group, no case was detected in those with MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have suggested an association between hepatitis B vaccination and the development of MS, a large body of research studies rejects the possibility of any association between them. [28][29][30] We also evaluated CMV in our case and control groups. While only one positive CMV infection was detected in the control group, no case was detected in those with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested an association between hepatitis B vaccination and the development of MS, a large body of research studies rejects the possibility of any association between them. 28 - 30 …”
Section: Discussionmentioning
confidence: 99%
“…In 2002, the National Academy of Sciences' Institute of Medicine, after having examined the published, peer-reviewed scientific and medical literature, concluded the lack of association between hepatitis B vaccination and the CNS demyelinating disease 72 . Additionally, studies that have examined the potential effect of hepatitis B vaccination on relapses in people diagnosed with the MS disease could not demonstrate an increased risk of relapse 73,74 .…”
Section: Influenza Infection or Vaccination As Probable Trigger Of Msmentioning
confidence: 99%
“…Live attenuated vaccines should be avoided for patients currently taking immunosuppressant medications and for a period of 3 months after discontinuation of treatment [Cahill et al 2010]. [Faure, 2005;Herroelen et al 1991;Monteyne and André, 2000;Ozakbas et al 2006;Salleras et al 2006]. The concerns relate, in part, to a report from France in the mid 1990s of a possible increase in autoimmune diseases, including MS, after hepatitis B vaccination.…”
Section: Vaccinationsmentioning
confidence: 99%
“…Concerns have been raised regarding a potential relationship between hepatitis B vaccination and MS relapses [Faure, 2005; Herroelen et al . 1991; Monteyne and André, 2000; Ozakbas et al . 2006; Salleras et al .…”
Section: Vaccinationsmentioning
confidence: 99%